Documentação pedagógica: uma abordagem construída no cotidiano de um berçário - Laissener, Rosiane Cristina (2021)
This dissertation aimed to study how the non-nursery Pedagogical Documentation enables the discussion of pedagogical practices with babies, favoring teacher education, considering the action of the teacher who registers and researches through this approach, and the requests, both as actors in the contexts of collective life. At first, it understands the conception of this approach, like the studies carried out by the pedagogies of Northern Italy, in the Region of Emillia Romana, as an instrument for reflection and planning of teaching actions in order to build forced experiences with babies as protagonists, and to support pedagogical practices and professional training. Adopting the techniques of observation, recording, document analysis, study, reflection and sharing with the school community, the Pedagogical Documentation was built, producing the data of this research and implementing its principles as a research method of the practice itself. Pedagogical Documentation as a research, reflection and communication tool can be a new way for the education of children and young children, making the school alive, producing culture, opportunities, which provokes thinking, reveals learning and gives meaning to everyday life from of the provocations it causes to the teaching action and, concomitantly, to the babies' actions. It proposes a review again and with a sensitive listening, enabling the communication of what has been lived through the sharing of mini-stories that show the discoveries of the researcher teacher and the babies as protagonists and authors.